KAMPANYE DIGITAL KONSERVASI FAUNA ENDEMIK KABUPATEN MERANGIN BERBANTUAN AI DAN MEDIA SOSIAL BAGI MASYARAKAT DIGITAL - Amrianto; Arista Ratih; Pitri Handayani; Eni Yulianti; Leni Marlina; Eko Wulandari; Schintia Yushika Anjelita; Budi Setiawan; Heri Hardinata (Hira Institute, 2026)
Conserving endemic fauna requires innovative approaches capable of reaching a broad audience cost-effectively. Merangin Regency is home to various protected endemic species such as the Great Argus (Argusianus argus) and the siamang (Symphalangus syndactylus) that continue to face threats. This community service initiative aimed to develop a digital conservation campaign by leveraging artificial intelligence (AI) and the social media platform for educational purposes. The implementation process involved three stages preparation, execution, and evaluation utilizing a digital ethnography approach that included social media metric analysis and the calculation of Engagement Rate (ER) based on reach. Six scientific articles were identified and used as primary sources for content development. Based on this material, ten educational posters were created and underwent content and design validation prior to publication. During the evaluation period, the posts garnered 4,590 views, 104 likes, 42 shares, 6 saves, and 1 comment, achieving an ER (Reach) of 3.33%, which falls into the